Towards an ethics perspective on the rational structure tradition of organisational communication (Communicare: Journal for Communication Studies in Africa, 2022)
The rational structure tradition of organisational communication is much referenced in academicliterature. The article outlines some key characteristics of this tradition. Some important theoriststo have contributed to this tradition include the great sociologist, Max Weber; the great championof scientific management, Fredrerick Taylor; and Luther Gulick, the champion of the division andcoordination of work. The MacDonaldised organisation is used to illustrate, not to evidence, oneform of organisation that has taken key aspects of the rational structure tradition to a fatal end.This article attempts to overview this tradition and thereby to contribute an ethics perspectivefocusing on the issue of the denial of the individual.